2018
DOI: 10.1186/s13075-018-1604-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study meta-analysis identifies five new loci for systemic lupus erythematosus

Abstract: BackgroundSystemic lupus erythematosus (SLE) is a common systemic autoimmune disease with a complex genetic inheritance. Genome-wide association studies (GWAS) have significantly increased the number of significant loci associated with SLE risk. To date, however, established loci account for less than 30% of the disease heritability and additional risk variants have yet to be identified. Here we performed a GWAS followed by a meta-analysis to identify new genome-wide significant loci for SLE.MethodsWe genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 47 publications
0
70
0
Order By: Relevance
“…Up to 100 susceptibility loci for polygenic, multifactorial SLE and more than 30 genes causing the monogenic form of SLE and SLE-like phenotypes have been described, yet they capture only a small proportion of heritability to lupus and other autoimmune diseases (Table 1) [1][2][3][4][5][6]. Discovery of novel or rare disease-causing gene variants in patients with early-onset SLE phenotype has had a significant contribution to the unraveling of molecular pathways involved in the disease pathogenesis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Up to 100 susceptibility loci for polygenic, multifactorial SLE and more than 30 genes causing the monogenic form of SLE and SLE-like phenotypes have been described, yet they capture only a small proportion of heritability to lupus and other autoimmune diseases (Table 1) [1][2][3][4][5][6]. Discovery of novel or rare disease-causing gene variants in patients with early-onset SLE phenotype has had a significant contribution to the unraveling of molecular pathways involved in the disease pathogenesis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we also identified significant lower expression of CD79A and CD79B (also known as Igα and Igβ, respectively). In a meta-analysis of GWAS results, Julià et al reported BCR signaling pathway as the most significant biological process and BCL10 and CD79A among top single markers associated with SLE [57]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…51 Some studies demonstrate that pathological elevation of these cytokines induce neurological dysfunctions (mainly in mouse models). NPLE CSF studies indicate INFα and IL6 as possibly related to CNS diffuse damage 52,53 .…”
Section: Neuropsychiatric Sle Pathophysiologymentioning
confidence: 99%
“…Although a strong genetic association was always evident, little was known of SLE genetics until the development of the genome wide association studies (GWAS). 54,55 These studies are hypothesis-free genome screening that link gene loci with disease phenotype in multifactorial diseases, as SLE. Prior to GWAS, a few genes were known to be associated to SLE, as is the case of the human leukocyte antigen (HLA) haplotypes.…”
Section: Sle Genetics and Epigeneticsmentioning
confidence: 99%